Implications of oxidative stress in chronic kidney disease: a review on current concepts and therapies - Sagar Verma; Priyanka Singh; Shiffali Khurana; Nirmal Kumar Ganguly; Ritushree Kukreti; Luciano Saso; Devinder Singh Rana; Vibha Taneja; Vinant Bhargava (The Korean Society of Nephrology, 2021)
Moderate levels of endogenous reactive oxygen species (ROS) are important for various cellular activities, but high levels lead to toxicity and are associated with various diseases. Levels of ROS are maintained as a balance between oxidants and antioxidants. Accumulating data suggest that oxidative stress is a major factor in deterioration of renal function. In this review, we highlight the possible mechanism by which oxidative stress can lead to chronic kidney disease (CKD). This review also describes therapies that counter the effect of oxidative stress in CKD patients. Numerous factors such as upregulation of genes involved in oxidative phosphorylation and ROS generation, chronic inflammation, vitamin D deficiency, and a compromised antioxidant defense mechanism system cause progressive detrimental effects on renal function that eventually lead to loss of kidney function. Patients with renal dysfunction are highly susceptible to oxidative stress, as risk factors such as diabetes, renal hypertension, dietary restrictions, hemodialysis, and old age predispose them to increased levels of ROS. Biomolecular adducts (DNA, proteins, and lipids) formed due to reaction with ROS can be used to determine oxidative stress levels. Based on the strong correlation between oxidative stress and CKD, reversal of oxidative stress is being explored as a major therapeutic option. Xanthine oxidase inhibitors, dietary antioxidants, and other agents that scavenge free radicals are gaining interest as treatment modalities in CKD patients.